SERVICE QUALITY IN CARRIER SERVICES - Huhtamäki, Jani (My University, 2008)
The goals of this study were to 1) examine which dimensions of service quality are the most important in carrier services 2) find a suitable tool for measuring service quality in carrier services, and 3) compare the customer’s vs service provider’s opinions about the importance of service quality dimensions in carrier services. Five generally accepted dimensions of service quality were found from the literature: tangibles, reliability, responsiveness, assurance and empathy. Tangibles means the physical facilities, equipment and appearance of service personnel. Reliability is the ability to perform the promised service dependably and accurately. Responsiveness means willingness to help customers and provide prompt service. Assurance is the knowledge and courtesy of service personnel and their ability to inspire trust in customers mind. Empathy is caring about the customer and the individualised attention the customer feels. A survey among three European carrier service providers and their customers was conducted to find out the importance of the five service quality dimensions. The Servqual instrument was chosen as a tool to measure the importance of the dimensions. The most important dimension of service quality in customer’s opinion was responsiveness followed by reliability, empathy and assurance. In service provider’s opinion, the most important dimension was reliability followed by responsiveness, assurance and empathy. Tangibles was rated as the least important service quality dimension in carrier services by every single respondent in both samples, customers and service providers. Service provider comments to the items in the Servqual questionnaire reveal that personal relations is a very important factor in carrier services. If several service providers offer nearly same price for the service, customers always choose the old service provider whose personnel they know and who they feel comfortable with. And they tolerate much more problems with ‘friends’.
Keywords: Service quality; Servqual; carrier service; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|